ANALYSIS OF ACCOUNT REPRESENTATIVE COMPETENCE AND ITS IMPACT ON INCREASING TAXPAYER COMPLIANCE - Endah Tri Wardhani; Murtanto (ZILLZELL MEDIA PRIMA, 2024)
The importance of the Account Representative's role in the business process of monitoring taxpayer compliance, it is necessary to find out what are the competencies of the Account Representative that have an impact on increasing taxpayer compliance. Data collection using a survey method with a questionnaire. Respondents in this study were Strategic Account Representatives of the Directorate General of Taxes. The results of the questionnaires collected were 111 questionnaires. Testing in this study was carried out using the Structural Equation Model Partial Square (SEM-PLS) statistical analysis model with SmartPLS software. The results showed that the knowledge variable had no effect in improving taxpayer compliance. Meanwhile, the experience and communication skill variables have a positive effect on taxpayer compliance.